Using less Quantum Resource for Probabilistic Controlled Teleportation of a Triplet W State - Ting Zhang; Xiu-Li Tu; Xian-Ming Wang; Xin-Wei Zha (Institute of Advanced Engineering and Science, 2012)
In a recent paper [CHIN. PHYS. LETT. Vol.26,No.7(2009)070306 ], DONG et al. proposed a scheme for probabilistic controlled teleportation of a triplet W state using combined non-maximally entangled channel of two Einstein–Podolsky–Rosen (EPR) states and one Greenberger–Horne–Zeilinger (GHZ) state. In this paper ,only using one Einstein–Podolsky–Rosen (EPR) state and one Greenberger–Horne–Zeilinger (GHZ) state,the scheme for probabilistic controlled teleportation of a triplet W state is presented. Furthermore, Comparing with the widely used Bell-State measurement, Alice performs orthogonal complete basis measurement in the current work. Then Bob can faithfully reconstruct the original state by performing relevant unitary transformations. The total probability of successful teleportation is only dependent on channel coefficients of EPR state and GHZ state. DOI: http://dx.doi.org/10.11591/telkomnika.v10i6.1546